Adsorption Study on Phenol from Bentonite doped with Zinc oxide: Synthetis, Characterization, Equilibrium, Kinetics, and Thermodynamic - Desnelli Desnelli; Delisa Rizkiani; Daniel Alfarado; Ferlinahayati Ferlinahayati; Heni Yohandini; Fatma Fatma; Ady Mara; Suheryanto Suheryanto; Elisa Nurnawati; Afreni Hamidah; Muhammad Said (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2024)
This study modified current bentonite with zinc oxide (ZnO) and investigated the performance of phenol adsorption. The material bentonite-ZnO was successfully synthesized and characterized with X-ray diffraction (XRD), scanning electron microscopy-energy dispersive X-ray (SEM-EDX), and Fourier transform infrared (FT-IR). The adsorption performance was determined by adsorption equilibrium, kinetics, and thermodynamic parameters. The adsorption, kinetic, and thermodynamic parameters were compared alternatively. The phenol adsorption capacity was obtained from Langmuir and Freundlich adsorption isotherm models, which for bentonite-ZnO was fit with both isotherm models (Langmuir R2 = 0,997 and Freundlich R2 = 0,9515) and was favorable than activated bentonite (n value bentonite-ZnO = 2.389; activated bentonite = 0,898). A kinetic model was tested with pseudo-first-order, pseudo-second-order, and intraparticle diffusion models which bentonite-ZnO and activated bentonite fit in the pseudo-second-order with an excellent agreement (R2 = 0,999). Several thermodynamic parameters such as enthalpy, Gibbs free energy, and bentonite-ZnO have an entropy more than zero (Î”S = 0.008 J/molK), which demonstrated the feasibility and spontaneity (Î”G < 0) and endothermic nature (Î”H = 3,056 kJ/mol) of the phenol adsorption process. Several thermodynamic parameters such as enthalpy, Gibbs free energy, and bentonite-ZnO have an entropy more than zero (Î”S = 0.008 J/molK), which demonstrated the feasibility and spontaneity (Î”G < 0) and endothermic nature (Î”H = 3,056 kJ/mol) of the phenol adsorption process. Based on the result data in this article, modified bentonite with ZnO has increased the ability for phenol adsorption than currently activated bentoniteKeywords: bentonite, adsorption equilibrium, adsorption kinetics, thermodynamics model, phenol, bentonite-ZnO